Analisis Hubungan Interpersonal Mahasiswa terhadap Dosen dalam Proses Bimbingan Skripsi. - Ristianti, Dina Hajja (ISLAMIC COUNSELING: Jurnal Bimbingan Konseling Islam, 2017)
One of the demands of the students success in learning in College is having a positive attitude towards lecturers so that students are able to build positive interpersonal relationships and communicate effectively with his professors. The number of complaints against the attitude of the supervising lecturer whose dibimbingnya are mainly in terms of communicating makes the background in this research. This research aims to know interpersonal relationships of college students toward professors in the process guidance of thesis. This research was conducted with descriptive method quantitative approach through. The population of the research was all students majoring in Islamic religious high school of Tarbiyah (STAIN) Curup the academic year 2010/2011 who are on semester 8 and is in the process of completion of the thesis. The number of samples as many as 69 people. The data obtained via the question form. The data were analyzed with the help of the program SPSS version 16.0. The results showed that interpersonal relationships of college students toward professors in terms of attitudes towards students appreciate lecturer in process guidance with thesis score tend to be occupied by students on the criteria either i.e. 74.5%. Interpersonal relationships of college students toward professors in terms of loyalty and tolerance attitudes of students toward professors in the process of graduation thesis guidance with a score that tend to be assigned to students on criteria either i.e. 66.6%. Interpersonal relationships of college students toward professors in terms of openness towards students in the process of graduation thesis guidance lecturer with a score that tend to be assigned to students at 60.2% i.e. enough criteria. Interpersonal relationships of college students toward professors in terms of friendliness toward students in the process of graduation thesis guidance lecturer with a score that tend to be assigned to students in not a good criteria i.e. 50.7%. Thus, the overall total score that tend to be assigned to students at enough where the score obtained is 75.08%. From this it can be concluded that interpersonal relationships of college students toward professors in the process of graduation thesis guidance in Curup STAIN is in the category of pretty